2005
DOI: 10.1080/13691050412331321285
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of sex education for young people in Lesotho

Abstract: This study aimed to identify the views of young people, parents and teachers concerning sex education in Lesotho. It was conducted at a time when the national government was considering the introduction of Population and Family Life Education, which includes sex education, into the national school curriculum. Forty-six focus group discussions were held with young people (10), parents (30) and teachers (6) to identify current sources of sex education and views of the proposed introduction of school-based sex ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
1
30
1
Order By: Relevance
“…Studies of school-based sexuality education recommend better quality education for teachers (Francis 2016;Kinsman et al 2001;Mturi and Hennink 2005). Teacher education that improves their knowledge and skills could increase teachers' confidence and comfort in teaching sexuality education (Ahmed et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of school-based sexuality education recommend better quality education for teachers (Francis 2016;Kinsman et al 2001;Mturi and Hennink 2005). Teacher education that improves their knowledge and skills could increase teachers' confidence and comfort in teaching sexuality education (Ahmed et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mturi and Hennink (2005) in a study on the sexual education of young people in Lesotho noted that, in particular, little is known about the attendance and curricula of traditional initiation schools. Results from that study suggest that, while the nature of sexual education in traditional initiation schools is relatively unknown, perceptions exist that the schools do not adequately educate participants about safe sex or the dangers of HIV/AIDS and may even encourage risky sexual behaviour (Mturi and Hennink 2005). Jeannerat (1997) in a study investigating female initiation schools in South Africa during the early 1990s observed similar criticisms of the sexual behaviour content of initiation school curricula.…”
mentioning
confidence: 97%
“…Still missing is a dedicated investigation into the impact of traditional rites of passage customs on the sexual behaviour of young people. Numerous studies have, however, demonstrated the positive association between formal curriculumbased school interventions and an improved awareness of HIV/AIDS and increased contraception use (Stanton et al 1998, Tiendrebeogo et al 2003, Kirby et al 2005, Mturi and Hennink 2005, Oshi et al 2005.…”
mentioning
confidence: 97%
“…Recent findings from research by Mturi and Hennink (2005) in Lesotho and Mathews et al (2006) in South Africa suggest that teachers are largely supportive of school-based sex education programmes; however, these studies do not examine teachers' attitudes and beliefs surrounding, for example, young people's sexual activity, what constitutes 'appropriate' content for sex education classes, and how these attitudes and beliefs may be gendered. As will be discussed, a consideration of teachers' identities as members of communities and wider sociocultural contexts suggests that school-based sex education should not simply be seen as a 'reliable, neutral and regulated source of information' (Mturi and Hennink 2005, 139), but as inevitably influenced by teachers' values which may limit young people's access to accurate and comprehensive SRH education.…”
Section: Introductionmentioning
confidence: 99%